FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL PANEN UDANG VANAME (Litopenaeus vannamei) DI PERTAMBAKAN KECAMATAN DEKET DAN KECAMATAN KARANGBINANGUN KABUPATEN LAMONGAN - Zulfaa Unzila Azizi; Farikhah Farikhah; Aminin Aminin (Jurnal Perikanan Pantura (JPP), 2022)
The Vannami Shrimp, also known as The White Shrimp, is one of many shrimp species, which is one of the most famous fish pond commodities with huge consumers. Deket and Karangbinangun District in Lamongan is the two district in East Java Province, Indonesia, that have massive produce and contribution to this Commodity Production. This Research uses Descriptive Methods; Descriptive Methods Research can usually be defined as the depiction or analysis of analytic descriptive or analytic quantitative. This Research used a survey method where the pond farmers from Deket District (n=48) and Karangbinangun District (58). The Average Age Farmers Data in Deket District is around 46 years old, while Karangbinangun District is approximately 53 years old. The Average Education Level Farmers Data in Deket District is about ten years old or in the Junior High School Level, while Karangbinangun is around seven years old. Also, in Deket District, about 37% are Full-Time Farmers while 63% are just Part-Time Farmers. The Width of Pond Data in Deket District is around 6158 Square Feet, while in Karangbinangun, around 4479,40 Square Feet. The result of this Research has been reserved, so the conclusion based on the statistic analysis using the T-Test and the Factors Correlation for Increasing Productivity has a significant impact in The T-Test on that Two District, The Significant Influencing Productivity Factor: “Age, Ponds Width, Community and Harvest Product” and The Factors that have a connection with Productivity including Respondent Factor (Age, Educational Level); Nature Factor (pond Width); and Input Factor (amount feed, fertilizer use).